Hubungan antara Faktor Motivasi Intrinsik dan Ekstrinsik dengan Prestasi Kerja: Kajian di Kalangan Pegawai Tentera Laut Di Raja Malaysia - Azizi, Hj. Ahmad Sarkawi (2009)
The purpose of this study is to determine relationship between intrinsic and extrinsic motivational factors towards job performance among Royal Malaysian Navy Logistic Officers (RMN). The study also aims to determine the association between variables of intrinsic and extrinsic motivational factors i.e. autonomy, pay and job characteristics with job performance. A total of 204 respondents involved in this study.Descriptive analysis technique by using mean as an indicator to evaluate the level of intrinsic and extrinsic motivational factors and job performance while Oneway ANOVA, Post Hoc Tests, Pearson Correlation and Multiple Regression being used to test the hipotesis.The result shows that the level of motivation and job performance among RMN Logictic Officers is at high level. The result shows that no significant different between job performance and demographic factors such as rank, years of service, age and academic qualification. On the other hand, it is clearly indicated that there is a significant different between intrinsic and extrinsic motivation with demographic factors whilst as for demographic factors of academic qualification there is no significant different with intrinsic and extrinsic motivation.The result also indicated that two intrinsic and extrinsic motivational factors i.e autonomy and job characteristics have a significant correlation with job performance while as for the pay factor, the result indicated it has no significant correlation with job performance. Analysis using multiple regression shows intrinsic and extrinsic motivational factors has it own impact towards job performance.